The Role of Youth in Strengthening Education and Literacy: The Case of The Loloan Youth Movement in Jembrana Bali - Sabarudin; Hasbil Ma’ani (Proceeding International Conference on Religion, Science and Education, 2023)
The purpose of this study is to describe and critically analyse the role of youth in East Loloan village in the education and literacy movement, both the underlying reasons, their implementation, and the obstacles faced. This qualitative research was conducted in 2022. Data were collected through in-person interviews, remote interviews, engaged observations, and document studies. This documentation study is mainly related to education and literacy activities informed through online media, Facebook, WhatsApp, and the Loloan Youth Movement Instagram. Observation activities are carried out directly at the Loloan Reading House and other places. Interviews were conducted with the Ward Chair, Youth Leaders, and several youths involved in Loloan Teaching and literacy activities at the Loloan Reading House. The analysis was carried out qualitatively using the analysis pattern that John Creswell developed. Data validity tests were performed using triangulation techniques and sources. The results of this study found: Pertama, the role of Muslim youth in the field of education through the Loloan Teaching program in east and west Loloan villages of Jembarana district. This passion drives Bali to help school children at the elementary school level prepare themselves for the national exam. Meanwhile, literacy activities at home continue the Loloan Mengajar program with a broader target: children and adolescents. Second, the implementation of educational activities through the Loloan Mengajar program is carried out by sending young students who are studying in the academic path to help teach in schools/madrasahs, from Mondays, Wednesdays and Saturdays, according to the agreed schedule. The literacy activities were carried out at the Loloan reading house, with a flagship program of 30 MB (30 minutes of reading), after which presentations and joint discussions. Third, The obstacles that arise and are faced, in addition to funding problems, are also related to the volunteer regeneration process, which takes work. Only some prepared cadres left the village because they were accepted to work in agencies far from where they lived in Loloan. Hence, it was challenging to spend their time and energy engaging in literacy activities at the Loloan Reading House.